Pembuatan Lampu Jalan Dengan Suplai Tenaga Surya di Desa Banjarwaru, Kecamatan Nusawungu - Sumardiono, Arif; Alimudin, Erna; Zaenurrohman, Zaenurrohman; Hazrina, Fadhillah; Susanti, Hera (Madani : Indonesian Journal of Civil Society, 2024)
Banjarwaru Village is located in Nusa Wungu District and has several hamlets connected to the main road as access to transportation facilities. The lack of street lighting hampers the activities of village residents, especially at night. Road points that do not have public street lighting are far from residents' homes, so they cannot use PLN electricity sources. Seeing the conditions explained above, the need for technology with energy sources that utilize renewable energy such as solar power to supply power to public street lights has been widely implemented. Making street lights with a solar power supply with the application of modern technology is the main priority in this community service activity. The main target objective of this Community Service is the Public Street Lighting Program through the manufacture of street lights with power supply from solar energy. The implementation method in this service is through observation and experiments in the field in the process of designing and manufacturing public street lights and handing over technology transfer to the community. The results of making public street lights with solar energy supply using Arduino Mega which functions to receive data from the LDR sensor and is continued with testing battery charging with solar power. The installation of the LDR sensor will help the efficiency of the lights because it will control the lights to turn on automatically. The results of the manufacture of public street lights also provided assistance and training to the Banjarwaru Village community regarding how the equipment works and the repair process if problems arise in the future.